Prevalence of asymptomatic sexually transmitted infections: a retrospective review of screening data from Desmond Tutu HIV Centre clinical trial cohorts from 2012 to 2017, Cape Town - Garnett, Nomcebo Precious (Department of Public Health and Family Medicine, 2020)
Background: The burden of Sexually transmitted infections (STIs) is high globally. The World Health Organisation (WHO) recommends syndromic management of these STIs, based on presentation with signs and symptoms, in resource-limited countries. Due to this syndromic approach, there is little current data on STI prevalence, including asymptomatic STIs, in high risk populations. Methods: We reviewed secondary data collected as part of the screening procedures of 6 clinical trials between 2012 and 2017 in Cape Town, South Africa. These trials recruited populations of different sexual orientation and gender, mostly key populations at risk of HIV and STI acquisition. Routine screening for STI symptoms and testing for Chlamydia, Gonorrhoea, Trichomonas, Syphilis and HIV was performed for all of the studies at screening/enrollment. Results: A total of 639 participants were screened; 411 (64.3%) self-identifying as female, 198 (31%) males, 29 (4.5%) transgender women and 01 (0.2%) transvestite. Median age was 20 years (IQR: 18-24), with the 15-24-year age category contributing 77% to the cohort. Laboratory testing diagnosed 239 (37.4%) people with STI infections in this cohort; only 28 (11.7%) people were symptomatic. 119 (88.8%) of Chlamydial, 64 (82.1%) of Gonorrhoeal, 23 (92%) of Trichomonal and 31(79.5%) of Syphilis infections elicited no signs and/or symptoms. Conclusion: A vast majority of STIs in this high-risk population were asymptomatic. Laboratory testing of causal organism was more reliable in diagnosing STIs than the use of signs and/or symptoms as recommended by WHO.